AN ANALYSIS OF EFFECT JOB DEMAND CONTROL-SUPPORT AND PROTECTION MOTIVATION ON COMPLIANCE IN FILLING INPATIENT CARE MEDICAL RECORD FILES - Maulidin, Muhammad (Universitas Aisyah Pringsewu, 2023)
An important indicator to determine the quality of service in a hospital is about the completeness of the hospital's medical record files. There are many problems arise due to incomplete medical record files and do not recorded neatly and regularly. The incident is due to lack of medical team awareness in recording all information or actions that would be given to the patient. The aim of this study is to analyse the effect of Job Demand-Control-Support and Protection Motivation on compliance in filling out Medical Record files at RSU ESHMUN Medan 2023. This study uses quantitative research method which is analytical in nature. The total sampling of this study is 115 active nurses at RSU ESHMUN Medan. The result of the study informs that there are very strong and significant effect among Job Demand-Control-Support and Protection Motivation on compliance in filling out Medical Record files at RSU ESHMUN Medan 2023. The variable that has the most influence on Obedience with filling in inpatient medical record files at RSU ESHMUN in 2023 is the Protection Motivation variable. It is recommended to RSU ESHMUN Medan to improve the administration pattern in order to all of nurses have the same job demands and receive the same support.